2004
DOI: 10.1076/jcen.26.2.190.28091
|View full text |Cite
|
Sign up to set email alerts
|

Conditional-Associative Learning in Eating Disorders: A Comparison With OCD

Abstract: The acquisition of conditional associations using neutral and individually threatening verbal stimuli was assessed in 16 females with anorexia nervosa (AN), obsessive-compulsive disorder (OCD), bulimia nervosa and normal controls, respectively. Groups did not differ in terms of age, sex, intelligence, depression, verbal memory and verbal fluency measures. Patients and controls were widely comparable on tests assessing neuropsychological functioning. In the conditional-associative learning (CAL)-task only anore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 26 publications
3
52
1
Order By: Relevance
“…However, OCs did not differ from the NACs when processing neutral and idiographic positive stimuli, suggesting OCs are capable of learning the contingency between the displays. Previous research on learning involving neutral and threat information in individuals with OCD compared to non-anxious individuals has shown OC's experience deficits in learning neutral stimuli but not threat stimuli (Leplow et al, 2002;Murphy et al, 2004). The authors of these two studies attribute this finding to an attentional bias that compensates for the general learning deficit.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, OCs did not differ from the NACs when processing neutral and idiographic positive stimuli, suggesting OCs are capable of learning the contingency between the displays. Previous research on learning involving neutral and threat information in individuals with OCD compared to non-anxious individuals has shown OC's experience deficits in learning neutral stimuli but not threat stimuli (Leplow et al, 2002;Murphy et al, 2004). The authors of these two studies attribute this finding to an attentional bias that compensates for the general learning deficit.…”
Section: Discussionmentioning
confidence: 92%
“…In the conditional associative learning studies by Leplow et al, (2002) and Murphy et al (2004) mentioned above, the individuals with OCD did not exhibit the same learning deficit when making associations between idiographically-selected threatening material and geometric shapes. Because any information processing bias in OCD is likely to be present for OCD-related information, and specifically, personally-relevant threat information, we were most interested in functioning involving this type of material.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The present meta-analysis shows a medium positive effect size on this test, indicating that patients with AN take significantly longer than the control group to complete this task. TMT switching is considered to be a test of divided attention Szmukler et al (1992) 6.7 0.93 (-0.00,1.85) Thompson (1993) 3.7 0.46 (0.04,0.89) Kingston et al (1996) 15.0 0.44 (-0.06,0.93) Mathias & Kent (1998) 11.8 0.01 (-0.68,0.71) Murphy et al (2004) 6.4 0.85 (0.36,1.34) Tchanturia et al (2004a) 11.9 0.85 (0.35,1.34) Tchanturia et al (2004b) 11 and in particular cognitive flexibility (Kortte, Horner, & Windham, 2002). A recent review has demonstrated a consistent set-shifting deficit in patients with eating disorders (Roberts et al, 2007), and it is possible that the longer time taken to complete the TMT test in the AN group is a reflection of this deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies (Hatch et al, 2010;Murphy, Nutzinger, Paul, & Leplow, 2004) administered the category condition of the VFT, and only one study (Murphy et al, 2004) employed the switching condition of the test. The results from these conditions were not meta-analysed.…”
Section: Verbal Fluency Testmentioning
confidence: 99%